Pengaruh Hypnobirthing Dengan Kejadian Asfiksia Pada Bayi Baru Lahir Di BPM Heny - Murni, Dewi Astuti; Sari, Endah Purwani; Winda, Desy (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2024)
One of the main causes of neonatal death is the incidence of neonatal asphyxia, which continues to increase every year. Neonatal asphyshia occurs in approximately 4 of every 1,000 live births in the United States. According to data reported to the Directorate of Family Health in 2020 in Indonesia, of all infant deaths, 72.0% (20,266 deaths) occurred at the age of 0-28 days. The causes of death of newborn babies in Indonesia are LBW (35.2%), asphyxia (27.4%), tetanus neonatorum (22.5%), congenital abnormalities (11.4%) and others (22.5% ). It happened because the transfer of O2 from mother to the fetus was blocked. Asuhan Sayang Ibu was provided to make mothers feel comfortable during the delivery process. In fact, sometimes the presence of family is not helpful in decreasing the pain and making the delivery easier. Hypnobirthing program was aimed to educate the pregnant mothers to be in harmony with the movement and rhythm of her body naturally during the delivery process. The objective of this study was to know the effect of hypnobirthing with the evidence of asphyxia on newborn babies. This study is an analysis study with prospective cohort design. The population of this study was all pregnant mothers TM III at BPM Henny. The sample was collected by using purposive sampling technique. The sample was divided into 2 groups that are radiated group and control group, each group consisted of 35 participants. The bi-variate analysis used Chi Square (X2) and the multivariate analysis used cox regression. The result of this study showed that there was the effect of hypnobirthing with the evidence of asphyxia on newborn babies (p= 0,012, RR=0.125). The result of multivariate analysis showed that hypnobirthing was a protective faktor (p=0.029, RR=0.096) and the delivery time was a risk factor of asphyxia (p=0.012, RR=5,421). It was concluded that hypnobirthing could decrease the rate of asphyxia on newborn babies.